GMSC-Derived Exosomes Combined with a Chitosan/Silk Hydrogel Sponge Accelerates Wound Healing in a Diabetic Rat Skin Defect Model - Shi, Quan; Qian, Zhiyong; Liu, Donghua; Sun, Jie; Wang, Xing; Liu, Hongchen; Xu, Juan; Guo, Ximin (Frontiers in Physiology, 2017)
Background: Delayed wound healing in diabetic patients is one of the most challenging complications in clinical medicine, as it poses a greater risk of gangrene, amputation and even death. Therefore, a novel method to promote diabetic wound healing is of considerable interest at present. Previous studies showed that injection of MSC-derived exosomes has beneficial effects on wound healing. In current studies, we aimed to isolate exosomes derived from gingival mesenchymal stem cells (GMSCs) and then loading them to the chitosan/silk hydrogel sponge to evaluate the effects of this novel non-invasive method on skin defects in diabetic rats. Methods: GMSCs were isolated from human gingival connective tissue and characterized by surface antigen analysis and in vitro multipotent differentiation. The cell supernatant was collected to isolate the exosomes. The exosomes were characterized by transmission electron microscopy, Western blot and size distribution analysis. The chitosan/silk-based hydrogel sponge was prepared using the freeze-drying method and then structural and physical properties were characterized. Then, the exosomes were added to the hydrogel and tested in a diabetic rat skin defect model. The effects were evaluated by wound area measurement, histological, immunohistochemical and immunofluorescence analysis. Results: We have successfully isolated GMSCs and exosomes with a mean diameter of 127 nm. The chitosan/silk hydrogel had the appropriate properties of swelling and moisture retention capacity. The in vivo studies showed that the incorporating of GMSC-derived exosomes to hydrogel could effectively promote healing of diabetic skin defects. The histological analysis revealed more neo-epithelium and collagen in the hydrogel-exosome group. In addition, the hydrogel-exosome group had the highest microvessel density and nerve density. Conclusions: The combination of GMSC-derived exosomes and hydrogel could effectively promote skin wound healing in diabetic rats by promoting the re-epithelialization, deposition and remodeling of collagen and by enhancing angiogenesis and neuronal ingrowth. These findings not only provide new information on the role of the GMSC-derived exosomes in wound healing but also provide a novel non-invasive application method of exosomes with practical value for skin repair.